From niche to mainstream: the dilemmas of scaling up sustainable alternatives. - Augenstein, Karoline; Bachmann, Boris; Egermann, Markus; Hermelingmeier, Verena; Nilger, Annaliesa; Jaeger-Erben, Melanie; Kessler, Alexandra; David P. M. Lam; Palzkill, Alexandra; Suski, Paul; Wirth, Timo von (ÖKOM, 2020)
At the heart oftransition research lies the question of how to "scale up" sustainable alternatives from a protected niche to the creation of mainstream practices. While upscaling processes are often seen as an essential element that contributes to societal transformation, upscaling itselfremains a fuzzy concept. We argue that some fundamental dilemmas of upscaling can be identified, for example, the different understanding of the concept by researchers and practitioners. The dilemmas should be addressed in a more reflexive way by those from the worlds of science and practice who are involved in collaborative research settings.
Keywords: Nachhaltige Stadtentwicklung; Transformation; Experiment; Nische; Reallabor; Forschungsergebnis; Umsetzung; Maßstab; Transdisziplinarität